Electrical shock-induced atrial fibrillation - Stojanović, Milovan; Ilić, Bojan; Deljanin-Ilić, Marina; Ilić, Stevan (Vojnosanitetski pregled, 2023)
Introduction. An electrical injury can cause various cardiac arrhythmias, such as asystole, ventricular fibrillation, sinus tachycardia, and heart blocks. However, it rarely causes atrial fibrillation (AF). Case report. The 47-year-old patient was admitted to the Emergency Department after receiving an electric shock (< 600 V). He subsequently lost consciousness, fell, and sustained back and head injuries. During the examination, the heart rate was irregular but with no heart murmurs. There was an entry wound on the front of the left thigh and an exit wound on the front of the neck. An electrocardiogram showed newly appearing AF. The laboratory tests showed no pathological deviation, and focus cardiac ultrasound showed that contractile force was preserved with no wall-motion abnormalities and normal left atrium dimensions. The patient was administered low-molecular-weight heparin subcutaneously and propafenone (600 mg) orally. At follow-up after 24 hrs, the electrocardiogram showed normal sinus rhythm. Conclusion. We reported a rare case of an electricity shock-induced AF, which was converted to sinus rhythm with the help of drug therapy. Although most cases of electricity shock-induced AF represent benign conditions that are self-limited, cardiac monitoring as a routine measure should be considered.